Analysis of the Influence of Information Technology and Characteristics Accountancy Management to BPRS Performance in Era 4.0 - Saleh, Sri Madona; Yenti, Elfina (TAMWIL : Jurnal Ekonomi Islam, 2024)
This research discusses the influence of information technology and management accounting characteristics on BPRS performance in the 4.0 era. The management accounting characteristics used consist of Board Scope, Timelines, Aggregation, and Integration. The aim of the research is to see the influence of information technology and management accounting characteristics on performance. The research was carried out using a quantitative approach with the research population being all BPRS in West Sumatra registered with the OJK in mid-2023 with a sample of BPRS management using a total sampling technique. The results of this research state that Information Technology has a significant influence on BPRS performance of 0.060 or 6% with a sig value of 0.046. Board scope has no influence on increasing or decreasing BPRS performance, because it has an influence of only 0.005 or 0.5% with a sig value of 0.868. Timelines have an influence on BPRS performance of 0.359 or 35.9% with a sig value of 0.001. Aggregation has no influence on increasing or decreasing BPRS performance by 0.085 or 8.5% with a sig value of 0.523. Integration has an influence on BPRS performance of 0.212 or 21.2%, with a sig value of 0.014. Simultaneously, information technology, Board Scope, Timelines, Aggregation and Integration have a significant influence on BPRS performance. The magnitude of the influence generated by the independent variables in this research is 25.5%.